Static routing for applications mapped on NoC platform using ant colony algorithms. (1st January 2012) - Silva Junior, Luneque Del Rio de Souza e; Nedjah, Nadia; Mourelle, Luiza de Macedo
Networks-on-chip (NoC) have been used as an interesting option in design of communication infrastructures for embedded systems, providing a scalable structure and balancing the communication between cores. Because several data packets can be transmitted simultaneously through the network, an efficient routing strategy must be used in order to avoid congestion delays. In this paper, ant colony algorithms were used to find and optimise routes in a mesh-based NoC. The routing optimisation is driven by the minimisation of total latency in packets transmission between tasks. The simulation results show the effectiveness of the ant colony inspired routing by comparing it with general purpose algorithms for deadlock free routing.